Application of horizontal well discontinuous chemical flooding technology in Bohai oilfield - Jian, Zhang; Dan, Liang; Liqi, Wang; Engao, Tang; Xianjie, Li; Wensen, Zhao (Frontiers in Energy Research, 2023)
Discontinuous chemical flooding technology of horizontal wells is a long-term development mechanism of horizontal wells established by combining and applying various oil displacement systems in different stages. Discontinuous chemical flooding not only ensures the injection capacity of chemical flooding stage, but also saves the operation cost of chemical flooding, and maximizes the economic benefits of crude oil production while improving the oil recovery. Based on the reservoir physical properties and fluid physical parameters of Bohai B oilfield, the development scheme of discontinuous chemical flooding in horizontal wells is studied on the basis of laboratory experimental evaluation. According to the optimization results of injection parameters, four types of slugs are set, i.e. front slug, main slug, auxiliary slug and secondary slug. A variety of agent systems such as gel, pre crosslinked particles, polymer and acid solution are used. The slug adjustment timing is determined by the monitoring data and the analysis results of production dynamic characteristics. Under the conditions of 0.07 PV/a injection rate and 0.49 PV slug dosage, the recovery efficiency of discontinuous chemical flooding can be improved by 10.4% compared with water flooding. After the implementation of the mine, the daily oil production of typical affected wells has shown an obvious upward trend, with a peak increase of 135% 151%, and a peak decrease of 15% in water content. After two years and six months of implementation, chemical flooding has achieved a cumulative increase of 66000 m3 compared with basic water flooding, with the oil increase accounting for 41% of the output of the whole stage. The effect of water reduction and oil increase is remarkable. The research results show that discontinuous chemical flooding can be popularized and applied in the oil fields developed by horizontal wells, so as to control the rapid rising trend of water cut in the middle and high water cut stage and further improve the oil recovery.